Листування В.В. Хвойки з Е. Міннзом як джерело для створення наукової біографії В.В. Хвойки - Колесникова, В.А. (Археологія, 2006)
В статті опубліковано матеріали листування двох науковців В.В. Хвойки та Е. Міннза від початку їхнього заочного знайомства в 1903 до 1913 рр. Результатам научных поисков и жизненному пути В.В. Хвойки посвящено ряд статтей и очерков, но еще не создано его достаточно полного научного исторического портрета, не проведено комплексного иследования его жизни и творчества. Для этого, вместе с изучением и обобщением многих материалов и документов, очень ценным представляется анализ личных контактов В.В. Хвойки с учеными и научными учреждениями в конце XIX — начале XX вв. Наиболее информативным источником является эпистолярное наследие ученого, его переписка с ведущими исследователями. This publication contributes to the development of the complete historical portrait of V.V. Hvoika and to the complex investigation of his life and work, though there are several articles and outlines devoted to the results of the scientific searching and course of life of this scholar. For the fulfillment of this task the analysis of personal contacts of V.V. Hvoika with the scholars and scientific institutions at the end of the 19th - the beginning of the 20th c. is of great value, together with the study and generalization of the content of many documents and materials. The most informative source in this case is epistolary heritage of the researcher, his correspondence with the leading scholars.